Book Review: Searching for Sustainability: Interdisciplinary essays in the Philosophy of conservation biology - Johan Hattingh (Environmental Association of Southern Africa, 2003)
Norton, B.G. (2003). Searching for Sustainability: Interdisciplinary essays in the philosophy of conservation biology. Cambridge: Cambridge University Press.